Symbiotic Dinoflagellates of the Giant Clam, Tridacna squamosa, Express Ammonium Transporter 2 at the Plasma Membrane and Increase Its Expression Levels During Illumination - Pang, Caryn Z.; Boo, Mel V.; Ip, Yuen K.; Chew, Shit F. (Frontiers in Marine Science, 2022)
Giant clams harbor dinoflagellates generally of the three genera (Symbiodinium, Cladocopium, and Durusdinium) of phototrophic Symbiodiniaceae. Coccoid dinoflagellates (alias zooxanthellae) are found mainly inside zooxanthellal tubules located in the colorful outer mantle. The symbionts need to obtain carbon, nitrogen and phosphorus from the host for growth and metabolism. The host can absorb exogenous ammonia through the ctenidium and assimilate it into glutamine. Although the host does not normally excrete ammonia, its hemolymph contains only low concentrations of ammonia, indicating that the symbionts can absorb and recycle the ammonia produced metabolically by the host. In this study, we had obtained from the outer mantle of the giant clam, Tridacna squamosa, three major ammonium transporter 2 (AMT2) sequences, one each for Symbiodinium spp. (Symb-AMT2), Cladocopium spp. (Clad-AMT2), and Durusdinium spp. (Duru-AMT2), which comprised 1341 bp, 1308 bp, and 1296 bp, respectively. The respective deduced amino acid sequences contained 447 (~ 46.5 kDa), 436 (~ 45.5 kDa), and 432 (~ 45.0 kDa) residues. Phenogramic and sequence similarity analyses confirmed that these sequences were derived from dinoflagellates. Zooxanthellae-AMT2 (Zoox-AMT2), which represented comprehensively AMT2 of Symbiodinium spp., Cladocopium spp., and Durusdinium spp. was localized at the dinoflagellates’ plasma membranes, indicating that it could partake in the absorption of ammonia from the luminal fluid of the zooxanthellal tubules. Zoox-AMT2 expression was detected in the outer mantle, inner mantle, foot muscle, hepatopancreas and ctenidium of T. squamosa, indicating that the coccoid dinoflagellates residing in all five organs had the potential of ammonia absorption. The outer mantle had the highest transcript level of Zoox-AMT2, and illumination upregulated the protein abundance of Zoox-AMT2 therein. Therefore, it can be deduced that the coccoid dinoflagellates residing in the outer mantle could augment the potential of ammonia absorption in alignment with photosynthesis as the assimilation of ammonia required an increased supply of carbon chains.